A Model for Biblical Worldview Development in Evangelical Christian Emerging Adults. Issue 3 (1st September 2020) - Erdvig, Roger C. S.
Abstract: The purpose of this grounded theory study was to develop a model of biblical worldview development for Evangelical Christians during emerging adulthood. Data were collected via personal worldview development timelines, semi-structured interviews, and a focus group. The study provided insight into a maturing biblical worldview, including growth in Sire's dimensions of worldview and also growth in three worldview dispositions: awareness of one's worldview, ownership of the process of worldview development, and commitment to meaningful processing. The Model for biblical Worldview Development in Evangelical Christian Emerging Adults suggests implications for educators who support worldview development in Evangelical emerging adults.